Elevated Plasma Levels of sIL-2R in Complex Regional Pain Syndrome: A Pathogenic Role for T-Lymphocytes? - Krishna D. Bharwani; Maaike Dirckx; Dirk L. Stronks; Willem A. Dik; Marco W. J. Schreurs; Frank J. P. M. Huygen (Mediators of Inflammation)
The immune system has long been thought to be involved in the pathophysiology of complex regional pain syndrome (CRPS). However, not much is known about the role of the immune system and specifically T-cells in the onset and maintenance of this disease. In this study, we aimed to evaluate T-cell activity in CRPS by comparing blood soluble interleukin-2 receptor (sIL-2R) levels between CRPS patients and healthy controls. CRPS patients had statistically significant elevated levels of sIL-2R as compared to healthy controls (median sIL-2R levels: 4151 pg/ml (Q3 − Q1 = 5731 pg/ml − 3546 pg/ml) versus 1907 pg/ml (Q3 − Q1: 2206 pg/ml − 1374 pg/ml), p<0.001, resp.). Furthermore, sIL-2R level seems to be a good discriminator between CRPS patients and healthy controls with a high sensitivity (90%) and specificity (89.5%). Our finding indicates increased T-cell activity in patients with CRPS. This finding is of considerable relevance as it could point towards a T-cell-mediated inflammatory process in this disease. This could pave the way for new anti-inflammatory therapies in the treatment of CRPS. Furthermore, sIL-2R could be a promising new marker for determining inflammatory disease activity in CRPS.